Earthquakes, catastrophic sediment additions and the response of urban stream communities - JS Harding; PG Jellyman (New Zealand Journal of Marine and Freshwater Research, 2015)
Disturbance events can regularly impact stream ecosystems; however, large‐scale catastrophic disturbances are rare. From September 2010 to September 2011 Christchurch City experienced over 8500 earthquakes including a magnitude 7.1. One consequence was catastrophic additions of silt and sand into waterways throughout the city. Of 161 km of permanent waterways, 102 km (63%) were affected by earthquake siltation. Benthic invertebrates and fish communities were compared across 16 streams with differing siltation. Invertebrate taxonomic richness decreased significantly (mean 17 taxa reduced to 10 taxa) and EPT taxa (Ephemeroptera, Plecoptera and Trichoptera) were removed entirely from streams receiving heavy siltation. Fish richness and density decreased significantly, with fish absent from some heavily silted streams. Many of these urban streams are sourced from springs and their stable flows and low gradient limit their ability to flush sediment. We predict that without human intervention there will be a long‐term sediment legacy and it may take many years for these streams to recover from this catastrophic disturbance.

Characterising riparian buffer zones of an agriculturally modified landscape - K Renouf; JS Harding (New Zealand Journal of Marine and Freshwater Research, 2015)
Riparian buffer zones are viewed as an important management tool for waterway protection. However, little qualitative or quantitative assessment has been made of their dimensions or composition. We surveyed 88 small agricultural waterways within the Canterbury region to characterise the width and vegetative composition of riparian ‘buffer’ zones. Less than 20% of buffer zones were 10 m or wider and approximately 65% ≤ 5 m wide. Mean plant diversity was lowest in buffers ≤ 5 m (four taxa) and highest in buffers 25–30 m wide (11 taxa), although 98% of all taxa recorded in the survey occurred within 5 m of waterways. Exotic pasture grasses, weeds and adventive trees and shrubs dominated riparian areas at all distances from the ‐side. Furthermore, buffer width and vegetation type did not differ with adjacent land use despite regional efforts to plant native vegetation and regulatory emphasis on reducing water contamination from intensifying land use practices.